(untitled) (Zoological Records and Reviews, 2023)
Temporary water bodies – seasonal ponds, vernal pools, rain-fed ditches, and ephemeral wetlands that lack permanent water connection – represent critical breeding habitats for a disproportionate number of European amphibian species, whose reproductive biology has evolved around the predictable seasonal hydroperiod of these systems and the relative absence of fish predators that characterises most temporary aquatic habitats. This review synthesises evidence from 176 primary studies (2003-2023) examining the breeding biology, reproductive success, and conservation status of European amphibians in temporary water body habitats across Mediterranean, Atlantic, Continental, and Boreal biogeographical regions. We document breeding phenology, reproductive strategies, larval development timing, hydroperiod requirements, and community assembly patterns for 24 European amphibian species with temporary water body associations. Breeding season onset has advanced by a mean 6.4 +- 1.8 days per decade across 18 monitored species (1990-2022), with Mediterranean species showing the greatest advancement (8.4 days/decade) driven by earlier and more variable winter rainfall patterns. Temporary pond loss across Europe exceeds 73% since 1900, with hydroperiod shortening due to climate change and groundwater abstraction documented at 68.4% of monitored temporary ponds. Minimum hydroperiod requirements for successful metamorphosis are species-specific (range 42-128 days) and represent the critical vulnerability for species in drying landscapes. Conservation interventions – pond creation, hydroperiod extension through impermeable liners, grazing management to maintain open structures – are evaluated against species-specific breeding biology requirements. Implications for EU Habitats Directive Article 17 assessment and Nature Restoration Law freshwater habitat restoration targets are discussed.